Feminist practice and poststructuralist theory - Weedon, Chris (Blackwell, 1987)
Feminist Practice and Poststructuralist Theory offers a clear and accessible introduction to poststructuralist theory, focusing on questions of language, subjectivity and power.
Keywords: 1900-1999; 1980-1989; discipline; europe; fem1000; linguistique; post-structuralisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences humaines; théories féministes